Perancangan Sistem Pelayanan Administrasi Kependudukan Kantor Desa Buahbatu Menggunakan PHP - Muhamad Iqbal Rifky Heryana; Mamok Andri S (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Buahbatu Village is a village located in Bandung Regency where data collection of its citizens is still conducting data collection of residents manually and the data storage of its residents is still in the form of files, where almost some villages in Bandung, data collection of residents has almost all used computerized methods and data storage. has been saved through the database. The purpose of making this system is expected to produce a computerized population administration service system. This program was developed using the waterfall model. This program was created using the PHP programming language integrated with the MySQL database. The end result of this program is that citizen data collection can be done computerized and stored in the database system, so that it can simplify and shorten the data collection of villagers.